1989
DOI: 10.1038/339355a0
|View full text |Cite
|
Sign up to set email alerts
|

A fusion protein required for vesicle-mediated transport in both mammalian cells and yeast

Abstract: A protein sensitive to N-ethylmaleimide catalyses the fusion of transport vesicles with Golgi cisternae in a mammalian cell-free system. By cloning and sequencing its gene from Chinese hamster ovary cells and by use of in vitro assays, we show that this fusion protein is equivalent to the SEC18 gene product of the yeast Saccharomyces cerevisiae, known to be essential for vesicle-mediated transport from the endoplasmic reticulum to the Golgi apparatus. The mechanism of vesicular fusion is thus highly conserved,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
296
0
9

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(312 citation statements)
references
References 28 publications
7
296
0
9
Order By: Relevance
“…Members of this gene family are present in prokaryocytes and eukaryotes, including bacteria (Confalonieri et al, 1994), yeast , plants (Feiler et al, 1995), and mammals (Egerton et al, 1992). They function in a variety of cellular processes, including vesicle-mediated transport (Eakle et al, 1988;Wilson et al, 1989;Babst et al, 1997), cell cycle regulation Clark-Maguire and Mains, 1994), peroxisome biogenesis , transcriptional regulation (Nelbock et al, 1990), and membrane fusion (Rabouille et al, 1995;Acharya et al, 1995). In S. cerevisiae alone, 22 di erent proteins with AAA-protein motifs have been identi®ed, suggesting that there are at least as many biological functions associated with this family (Beyer, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of this gene family are present in prokaryocytes and eukaryotes, including bacteria (Confalonieri et al, 1994), yeast , plants (Feiler et al, 1995), and mammals (Egerton et al, 1992). They function in a variety of cellular processes, including vesicle-mediated transport (Eakle et al, 1988;Wilson et al, 1989;Babst et al, 1997), cell cycle regulation Clark-Maguire and Mains, 1994), peroxisome biogenesis , transcriptional regulation (Nelbock et al, 1990), and membrane fusion (Rabouille et al, 1995;Acharya et al, 1995). In S. cerevisiae alone, 22 di erent proteins with AAA-protein motifs have been identi®ed, suggesting that there are at least as many biological functions associated with this family (Beyer, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The ®rst protein associated with membrane fusion is SEC18, whose mutant blocks the fusion of transport vesicles with Golgi cisternae in the protein secretory pathway (Eakle et al, 1988). Its equivalent in higher organisms is NSF (N-ethylmaleimide-sensitive fusion protein), an essential component of SNAP/SNARE fusion machinery that mediates protein transport from the ER to the Golgi complex (Wilson et al, 1989). PAS is another member of the subfamily involved in membrane fusion events, whose mutant is incapable of forming peroxisomes from smaller precursors .…”
Section: Discussionmentioning
confidence: 99%
“…[1,2]). NSF is an ATPase and contains two homologous nucleotide-binding regions [3,4], and SNAPs mediate the association of NSF with membranes [5,6]. S611ner et al [7] identified VAMP-2 [8,9], syntaxin 1 [10][11][12], and SNAP-25 [13] as SNAP receptors (SNAREs).…”
Section: Introductionmentioning
confidence: 99%
“…NSF and SNAPs were originally detected as factors required for transport through the Golgi in in vitro assays [6,7,21] and the yeast homologues of these proteins, secl8 and secl7, are essential for secretion in vivo [22]. In Golgi transport assays and in the formation of a Golgi membrane derived 20S complex, a-and ]3-SNAP appear to be functionally redundant whereas y-SNAP binds to different membrane sites and has a distinct role in stabilisation of the 20S complex [23,24].…”
Section: Introductionmentioning
confidence: 99%